The decline of adult smallpox in eighteenth-century London - Davenport, Romola (Econ Hist Rev, 2011)
Smallpox was probably the single most lethal disease in eighteenth-century Britain, but was a minor cause of death by the mid-nineteenth century. Although vaccination was crucial to the decline of smallpox, especially in urban areas, from the beginning of the nineteenth century, it remains disputed the extent to which smallpox mortality declined before vaccination. Analysis of age-specific changes in smallpox burials within the large west London parish of St Martin-in-the-Fields revealed a precipitous reduction in adult smallpox risk from the 1770s, and this pattern was duplicated in the east London parish of St Dunstan's. Most adult smallpox victims were rural migrants, and such a drop in their susceptibility is consistent with a sudden increase in exposure to smallpox in rural areas. We investigated whether this was due to the spread of inoculation, or an increase in smallpox transmission, using changes in the age patterns of child smallpox burials. Smallpox mortality rose among infants, and smallpox burials became concentrated at the youngest ages, suggesting a sudden increase in infectiousness of the smallpox virus. Such a change intensified the process of smallpox endemicization in the English population, but also made cities substantially safer for young adult migrants.